Tailored Therapies for Cardiogenic Shock in Hypertrophic Cardiomyopathy: Navigating Emerging Strategies - George E. Zakynthinos; Ioannis Gialamas; Vasiliki Tsolaki; Panteleimon Pantelidis; Athina Goliopoulou; Maria Ioanna Gounaridi; Ioanna Tzima; Andrew Xanthopoulos; Konstantinos Kalogeras; Gerasimos Siasos; Evangelos Oikonomou (Journal of Cardiovascular Development and Disease, 2024)
Hypertrophic cardiomyopathy (HCM) is a complex and heterogeneous cardiac disorder, often complicated by cardiogenic shock, a life-threatening condition marked by severe cardiac output failure. Managing cardiogenic shock in HCM patients presents unique challenges due to the distinct pathophysiology of the disease, which includes dynamic left ventricular outflow tract obstruction, diastolic dysfunction, and myocardial ischemia. This review discusses current and emerging therapeutic strategies tailored to address the complexities of HCM-associated cardiogenic shock and other diseases with similar pathophysiology that provoke left ventricular outflow tract obstruction. We explore the role of pharmacological interventions, including the use of vasopressors and inotropes, which are crucial in stabilizing hemodynamics but require careful selection to avoid exacerbating the outflow obstruction. Additionally, the review highlights advancements in mechanical circulatory support devices such as extracorporeal membrane oxygenation (ECMO) and left ventricular assist devices (LVADs), which have become vital in the acute management of cardiogenic shock. These devices provide temporary support and bridge patients to recovery, definitive therapy, or heart transplantation, which remains a critical option for those with end-stage disease. Furthermore, the review delves into the latest research and clinical trials that are refining these therapeutic approaches, ensuring they are optimized for HCM patients. The impact of these treatments on patient outcomes, including survival rates and quality of life, is also critically assessed. In conclusion, this review underscores the importance of a tailored therapeutic approach in managing cardiogenic shock in HCM patients, integrating pharmacological and mechanical support strategies to improve outcomes in this high-risk population.